Primitive human hematopoietic cells give rise to differentially specified daughter cells upon their initial cell division - Giebel, Bernd; Zhang, Tao; Beckmann, Julia; Spanholtz, Jan; Wernet, Peter; Ho, Anthony Dick; Punzel, Michael (Blood, 2006)
It is often predicted that stem cells divide asymmetrically, creating a daughter cell that maintains the stem-cell capacity, and 1 daughter cell committed to differentiation. While asymmetric stem-cell divisions have been proven to occur in model organisms (eg, in Drosophila), it remains illusive whether primitive hematopoietic cells in mammals actually can divide asymmetrically. In our experiments we have challenged this question and analyzed the developmental capacity of separated offspring of primitive human hematopoietic cells at a single-cell level. We show for the first time that the vast majority of the most primitive, in vitro-detectable human hematopoietic cells give rise to daughter cells adopting different cell fates; 1 inheriting the developmental capacity of the mother cell, and 1 becoming more specified. In contrast, approximately half of the committed progenitor cells studied gave rise to daughter cells, both of which adopted the cell fate of their mother. Although our data are compatible with the model of asymmetric cell division, other mechanisms of cell fate specification are discussed. In addition, we describe a novel human hematopoietic progenitor cell that has the capacity to form natural killer (NK) cells as well as macrophages, but not cells of other myeloid lineages.